A case report of primary breast angiosarcoma: An uncommon malignancy - Ayesha Afzal, MBBS, FCPS; Muhammad Junaid Tahir, MBBS; Asma Asghar, MBBS FCPS; Hira Yaqub, MBBS; Anis Ur Rehman, MBBS, FRCR; Aamer Iftikhar, MBBS, FRCR (Radiology Case Reports)
Angiosarcoma of the breast is a rare and aggressive form of cancer that originates from vascular or lymphatic tissues, representing only 0.04% of malignant breast lesions. Variance in the clinical, pathological, and radiological presentations often leads to challenges in diagnosis. We present a case of a 32-year-old lactating female having a painless swelling in her right breast for 6 months, with a significant increase in size in 1 month. Clinical assessment indicated the presence of a mass at the superior edge of the areola, with associated bluish skin discoloration. Ultrasonography revealed a vascular lesion characterized by mixed echogenicity. A core biopsy confirmed the diagnosis of angiosarcoma. Imaging studies, including computed tomography (CT) and bone scans, ruled out distant metastases. Subsequently, surgical excision was performed, and histopathological analysis reaffirmed the diagnosis of angiosarcoma. Radiotherapy was deemed unsuitable due to the potential risk of recurrence or radiation-induced secondary angiosarcoma. This case highlights the necessity of a multidisciplinary approach in optimizing diagnosis and treatment, with surgical excision playing a pivotal role in disease management.